The expression of Rpb10, a small subunit common to RNA polymerases, is modulated by the R3H domain-containing Rbs1 protein and the Upf1 helicase - Cieśla, Małgorzata (Nucleic Acids Res, 2020)
The biogenesis of eukaryotic RNA polymerases is poorly understood. The present study used a combination of genetic and molecular approaches to explore the assembly of RNA polymerase III (Pol III) in yeast. We identified a regulatory link between Rbs1, a Pol III assembly factor, and Rpb10, a small subunit that is common to three RNA polymerases. Overexpression of Rbs1 increased the abundance of both RPB10 mRNA and the Rpb10 protein, which correlated with suppression of Pol III assembly defects. Rbs1 is a poly(A)mRNA-binding protein and mutational analysis identified R3H domain to be required for mRNA interactions and genetic enhancement of Pol III biogenesis. Rbs1 also binds to Upf1 protein, a key component in nonsense-mediated mRNA decay (NMD) and levels of RPB10 mRNA were increased in a upf1Δ strain. Genome-wide RNA binding by Rbs1 was characterized by UV cross-linking based approach. We demonstrated that Rbs1 directly binds to the 3′ untranslated regions (3′UTRs) of many mRNAs including transcripts encoding Pol III subunits, Rpb10 and Rpc19. We propose that Rbs1 functions by opposing mRNA degradation, at least in part mediated by NMD pathway. Orthologues of Rbs1 protein are present in other eukaryotes, including humans, suggesting that this is a conserved regulatory mechanism.